The Effect of the Elements Co and Ni on Wear Behaviour of Bronze Alloys Produced by the Hot Pressing Method - Yildiz, Tulay; Kati, Nida; Yilmaz, Alaattin (Springer India, 2021)
In this study, samples were produced via the Hot Isostatic pressing method by adding the elements Ni and Co at different rates into Cu-Sn (85/15) alloys. Due to their physical, thermal, and wear properties, Cu-Sn bronze alloys are widely used in journal bearings and bushings in automotive applications. In order to improve the mechanical properties of Cu-Sn alloys, it was aimed to increase their hardness and wear resistances by adding the elements Ni and Co at certain rates. By taking SEM images of the produced samples, their microstructures were examined, the hardness measurements were carried out using Brinell hardness measurement method and the porosity rates were determined based on Archimedes' principle by conducting density measurements. Additionally, the effects of Ni and Co elements added to improve the wear properties of these alloys on wear were investigated.
Keywords: Cu– Sn alloy; Ni and Co; Hot isostatic pressing; Adhesive wear